The comprehensive verses according to Ibn Kathir in his interpretation of the Great Qur’an (Islamic Sciences Journal, 2024)
ABSTRACTPraise be to Him who deposited secrets and wisdom in His Book, and may God’s blessings and peace be upon our Prophet Muhammad and his family and all his companions.As for what follows:I followed the words of Ibn Katheer in his interpretation regarding the description of the verses and surahs of the Qur’an with a description or characteristic, whether from the pure Sunnah or from the sayings of the righteous predecessors, and I explained the classification of scholars in the books of the sciences of the Qur’an for this subject, then I cited the differences of opinion among scholars regarding the ruling on saying that some parts of the Qur’an are preferred over others. Then I translated it for the author in a brief translation that was not commensurate with his ability and status due to the narrowness of the situation. Then I divided the topic into eight demands, and divided the good demand into seven paragraphs so that the author could talk about it at length. Then I came up with some modest results, and praise first and last.Praise be to God, Lord of the Worlds, and may God’s blessings and peace be upon our Prophet Muhammad and his family and all of his companions.
Keywords: Verses, Al-Jami’ah, Ibn Kathir, Tafsir, The Great Qur’an.